SIMULATION STUDY ON CAVING PROCESS OF CAVING COAL HYDRAULIC SUPPORTS BASED ON EDEM - MAO Jun; LIU SiYang; ZHANG Kun; LIU XinYan; WANG Jin (Jixie qiangdu)
In order to study the caving process of caving coal hydraulic support and the breaking law between immediate roof and basic roof,Taking the ZF15000/28/52 export caving hydraulic support as the research object, establish a three-dimensional simulation model by EDEM（an discrete element simulation software）,Taking Comprehensive consideration the effects of coal and rock particles and composition on coal caving,finally obtained the coal caving process with hydraulic support, the movement trend and velocity of coal and rock particles and the bond force chain of immediate roof and the basic roof,The simulation results are basically consistent with the actual coal caving process, which provides a new way to study the caving process of hydraulic support.